Acute necrotizing fasciitis developed due to Staphylococcal infection during neonatal varicella - Tuncer, Oǧuz; Ataş, Bülent; Kırımi, Ercan; Akbayram, Sinan; Atik, Bekir; Çaksen, Hüseyin (Journal of Pediatric Infectious Diseases, 2006)
Although varicella acquired during childhood normally has a benign course, complications may occur during the course of the disease. Cellulitis sometimes occurs as a result of bacterial superinfection. When caused by A-group Streptococci cellulitis may evolve into necrotizing fasciitis leading to necrosis of deep tissues. We have found treatment using parenteral antibiotics, intensive supplementary therapy and surgical debridement of necrotic tissues to be effective. A case of Staphylococcal necrotizing fasciitis in a neonate is reported.
Keywords: Neonatal varicella; acute necrotizing fasciitis